2015
DOI: 10.1213/ane.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for Cesarean Delivery in the Czech Republic

Abstract: The rate of neuraxial anesthesia use for cesarean delivery has increased in the Czech Republic in the last 2 decades. However, the current rate of general anesthesia is high compared with other Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
4
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 11 publications
3
15
4
5
Order By: Relevance
“…One report from Georgia cited lack of governmental funding for supplies, lack of familiarity of anesthesia staff with current techniques and evidence-based guidelines, and limited availability of appropriate local anesthetics as possible reasons (10). Another survey of RA use from the Czech Republic cited patient fear over the safety of RA and lack of acceptance by obstetric providers (9), similar to a report of an ongoing collaboration in China between Chinese and American anesthesia providers (11). …”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…One report from Georgia cited lack of governmental funding for supplies, lack of familiarity of anesthesia staff with current techniques and evidence-based guidelines, and limited availability of appropriate local anesthetics as possible reasons (10). Another survey of RA use from the Czech Republic cited patient fear over the safety of RA and lack of acceptance by obstetric providers (9), similar to a report of an ongoing collaboration in China between Chinese and American anesthesia providers (11). …”
Section: Introductionmentioning
confidence: 68%
“…RA is associated with a lower maternal mortality risk compared to general anesthesia (GA) in both high and low- and middle-income countries (LMICs) (37). Despite this recognition, many Eastern European countries report much lower rates of RA use for CD and neuraxial analgesia for labor (NAL) (8, 9). Barriers to implementation in such settings are varied.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of GA for CS in the hospital was described as 29.5% in 2014 (Stourac et al., 2015). In our study group, we reported 35% C‐sections, 2.85% assisted vaginal deliveries, and 15.7% parturients received EOA.…”
Section: Discussionmentioning
confidence: 99%
“…We reported six cases of obstetric indications in 25 cases of CS and another 18 cases as neurological indications due to MS. One literature review and meta‐analysis showed possible higher prevalence of C‐sections (between 9.6% and 41.10%) as a reflection of cultural, religious, geographical and regional backgrounds (Finkelsztejn et al., 2011). Another remarkable finding is the rate of GA for CS in the MS group (64%) that is more than twice as high asthe routine CS rate in the University Hospital Brno (29.5%) (Stourac et al., 2015). The GA rate for an obstetric patient in this investigation exceeds by far that reported by Drake et al.…”
Section: Discussionmentioning
confidence: 99%
“…5 Beberapa obat anestesi lokal, yaitu ropivakain dan levobupivakain dapat menjadi obat pilihan pada blokade neuroaksial karena memiliki toksisitas yang rendah meskipun diberikan dalam jumlah yang banyak. 6 Bupivakain merupakan obat anestesi lokal yang sangat kardiotoksik, namun masih menjadi obat anestesi lokal yang paling banyak digunakan oleh dokter anestesi 7 termasuk di Jawa Barat. Hal ini dikarenakan harganya yang lebih murah dan mudah didapat dibanding dengan ropivakain maupun levobupivakain.…”
Section: Pembahasanunclassified